Animals We Eat and Animals We Care for: Hegel’s Ambiguous Notion of the Animal as Soul - Timo (Ethics in Progress, 2025)
There is a fundamental contradiction in most people’s behaviour towards animals. On certain occasions, we pet, nurture, name and even talk to them. On other occasions, we put up with or even endorse slaughtering and eating them. While this contradiction takes on a particular shape in times of modern slaughterhouses, petting zoos and pet culture, the contradiction itself is not modern at all. The ancient Chinese Confucian classic Mencius already speaks of the noble person who cultivates compassion while staying out of the kitchen (where animals are butchered). Modern philosophy begins with Descartes’ firm proposal of the animal machine, that is, of animal life as natural automaton or mechanism. By contrast, Hegel conceives of the animal as soul and the highest articulation of self-determination in nature. Yet Hegel’s position is ambiguous: he provides everything one needs to acknowledge animal subjectivity but does not propose any dignity of the animal. Drawing mostly from the Science of Logic and the Philosophy of Nature along with his discussion of Descartes in the Lectures on the History of Philosophy, I examine Hegel’s account of animal subjectivity. I conclude by pondering why Hegel, nevertheless, does not attribute any dignity to the animal.